Pengembangan Sumber Daya Manusia melalui Program Pelatihan Berkelanjutan - Rahmayanti, Sri; Misral, Misral (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
Organisations need development and training to enable employees to perform as expected by the organisation. Development and Training is not only needed for new employees but for all employees. Training improves skills in the short term, while development improves employees' abilities to prepare them for greater tasks in the future. Development and Training aims for equity in the development of human resource quality through various processes, methods of education planning, training and employee management to achieve satisfactory results. Because the quality of human resources is the asset of every organisation, in accordance with the expectations of the organisation.